THEORETICAL APPROACHES TO THE CREATION OF PEDAGOGICAL CONCEPTS - Khasanov Abdushokhid Abdurashidovich; Khasanova Sabokhat Sadullaevna (American Journals, 2023)
This article presents theoretical approaches to the creation of pedagogical concepts of the concept of implementation based on certain rules in the use of modern methods of teaching students in higher education institutions.
Keywords: Pedagogy, system, methodology, approach, electronic education, concept, individual education, digital education, rule, direction, culture.